Diversity of Rhizobium leguminosarum in the Palouse of Eastern Washington - Mahler, R. L. (1978)
Serology, antibiotic resistance, litmus milk reaction, and ability to fix nitrogen in peas were methods employed in studying the diversity of Rhizobium leguminosarum. The two serogroups identified were related to the position on the soil slope where isolated were taken.